Pengaruh Terpaan Promosi Penjualan dan Terpaan E-Word of Mouth #ShopeeHaul di TikTok terhadap Perilaku Impulse Buying - Gabby Aurelia; Djoko Setyabudi; S. Rouli Manalu (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
This study aims to see the effect of exposure to sales promotions (X1) and exposure to e-Word of Mouth #ShopeeHaul on TikTok (X2) on impulsive buying behavior (Y). With the emergence of the Covid-19 pandemic, 61% claimed to have experienced a decrease in income, but on the other hand, online shopping and e-commerce sales increased by 91%, the majority is dominated by Shopee. The success of e-commerce in the Indonesian online store requires a strategy, one of which is to spread product information on social media in the form of sales promotion and electronic word of mouth, one of which is TikTok. However, it turns out that these two things can affect consumer behavior in shopping and even trigger impulsive buying behavior. This study uses previous research as the basis for deriving hypotheses and uses simple linear regression analysis with non-probability sampling technique with the convenience sampling method. The sample is 100 people with the characteristics of social media users aged 18-40 years in Indonesia. The hypothesis test results of sales promotion exposure (X1) on impulsive buying behavior (Y) show a significance value of 0.007 which means there is a significant effect, and the hypothesis is accepted. The significance value of the e-WOM #ShopeeHaul TikTok exposure test (X2) on impulsive buying behavior (Y) is 0.031, which means there is a significant effect, and the hypothesis is accepted. This study hopes that related parties, especially Shopee consumers and sellers, can better understand impulse buying due to sales promotions exposure and e-WOM #ShopeeHaul exposure which has a negative impact. Therefore, consumers must be more careful in using their money, so they are not used to living extravagantly, especially during this pandemic. However, impulse buying behavior can benefit the seller and Shopee, so this research is also expected to create new ideas for Shopee sellers to increase their sales